Urban infrastructure : finance and management - Wellman, Kath.; Spiller, Marcus; Wiley eBooks (Chichester : Wiley, 2012)
"Urban Infrastructure: finance and management is posited on a strong belief that the physical structure of cities and the efficiency of infrastructure services delivered are driven by efficiencies within individual infrastructure sectors, lessons learnt across these sectors and the ability to co-ordinate and integrate sectors to generate economies of scale. This necessitates an interdisciplinary approach, integrating knowledge from finance, governance, planning and management as well as the characteristics of the individual urban infrastructure sectors involved. Here it is not only about getting the initial decisions and policy settings right, but also ensuring effective implementation. A major theme running through the book is the nature of institutions and the governance structures responsible for delivery and management of urban infrastructure and the decision making processes involved. The editors have taken a deliberately pragmatic approach to the finance and management of urban infrastructure; chapters are cross-sectorial and present both theory and practice. This book is for students and practitioners in policy, planning, urban management, infrastructure finance and management."--Publisher's website.
Introduction -- Urban Management Principles and Instruments -- Urban Infrastructure: Productivity, Project Evaluation, and Finance -- Private-Public Partnerships: Transaction Analysis and the Case of Urban Motorways -- Land Management and Planning Legislation -- Financing and Managing Urban Water -- Financing and Managing Urban Energy Systems -- Financing and Managing Urban Transport -- Principles and Systems for Coordination of Infrastructure Investment across Portfolios.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Infrastructure (Economics) -- Finance; Infrastructure (Economics) -- Australia -- Finance -- Case studies; Public works; Urban economics; Urban policy; Infrastructure (Economics) -- Australia -- Finance; Infrastructure (Economics) -- Finance; Environmental Studies; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Infrastructure (Economics) -- Finance; Public works; Urban economics; Urban policy; Australia; Samhällsplanering.; Stadsplanering; Electronic books